2020
DOI: 10.9734/afsj/2020/v14i330133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Treatment on Physicochemical Stability and Antioxidant Properties of Locally Available Underutilized Star Fruit Juice

Abstract: Industrial processing of the fruit juice is responsible for the changes in some quality attributes. Thermal treatment is a most applicable operation for any processing and it affects the physicochemical and antioxidant properties of the juice. This study was conducted to observe the changes in some physical properties and the bioactive compounds of star fruit (Averrhoa carambola L.) juice during thermal treatment at 70°C, 80°C and 90°C for 10, 20, 30 and 40 min by a temperature-controlled water bath. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…However, the vision of all samples is quite similar, its color was white. This result agreed with Shourove et al (2020) and Chutintrasri and Noomhorm (2007), those authors found the ∆E value of pineapple puree and star fruit juice, respectively, increased with time and treatment temperature. The value has different letters superscript show statistically significant differences at the α = 0,05 confidence level.…”
Section: Effect Of Thermal Treatment On Color Properties Changessupporting
confidence: 91%
“…However, the vision of all samples is quite similar, its color was white. This result agreed with Shourove et al (2020) and Chutintrasri and Noomhorm (2007), those authors found the ∆E value of pineapple puree and star fruit juice, respectively, increased with time and treatment temperature. The value has different letters superscript show statistically significant differences at the α = 0,05 confidence level.…”
Section: Effect Of Thermal Treatment On Color Properties Changessupporting
confidence: 91%
“…A previous study reported that the increasing temperature at a certain level accelerates the extraction, but after that level, it decreased because of the reduced stability of phenolic compounds (Dorta et al, 2012). The lower TPC value was also observed at the hightemperature treatment of star fruit juice due to the destabilization of the phenolic structure (Shourove et al, 2020). The present study revealed, Moringa leaves as a potential source of polyphenol, which Moringa leaves had contained much higher total polyphenol (mg GAE/ 100g) than some Indian fruits and vegetables such as pomegranate (671.1 ± 18.5), mango (440.6 ± 16.6), kinnow (354.9 ± 12.5), banana (362.4 ± 17.2), beetroot (909.5 ± 37.4), bringal (292.3 ± 12.7), bitter gourd (226.5 ± 10.5), black carrot (1028.6 ± 23.4), spinach (233.5 ± 20.2) (Singh et al, 2016).…”
Section: Resultsmentioning
confidence: 94%
“…Again, the antioxidant value was found to decrease with the increasing temperature and the extraction time, which maybe because of the destruction of the chemical composition of the polyphenolic compounds, ascorbic acid and chlorophyll content of the Moringa leaf (Sreelatha and Padma, 2009;Nobossé et al, 2018). Those study revealed Moringa leaves as a potential source of antioxidant compounds, which showed higher antioxidant activity than some typical fruit juice such as: lemon (63%), orange (61%), star fruit (60.19%), mandarin (52%), grapefruits (58%) (Shourove et al, 2020).…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 95%
“…2 showed that total flavonoid contents of the Taikor had a significantly (p ≤ 0.05) higher amount of flavonoid (148.18 ± 0.40 mg QE/100 ml) than the Roselle (118.87 ± 1.09 mg QE/100 ml), Olive (92.30 ± 0.80 mg QE/100 ml), and Jujube (90.19 ± 0.30 mg QE/100 ml). All the fruits were found to contain higher amounts of flavonoids than another underutilized fruit Carambola (2.56 ± 0.40 mg QE/100 ml) as reported by Shourove et al (2020). Mudoi et al (2012) also reported that the methanolic extract of G. pedenculata had contained 71.4 ± 0.84 mg QE/100 g on dry weight basis.…”
Section: Resultsmentioning
confidence: 58%